MOTIVASI SEBAGAI PEMODERASI PENGARUH KOMPETENSI DAN TEKNOLOGI INFORMASI PADA PENERAPAN AKUNTANSI BERBASIS AKRUAL - Sari, Fenty Herlina; Suprasto, Bambang; Dwirandra, A.A.N.B (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
The implementation of accrual basis accounting in the government sectoris based on the consideration that it can provide more complete information, provide information in government operations, the evaluation of efficiency and effectiveness and adherence to the regulations. This study aimed to analyze the effect of the competency of human resources (HR), information technology on the implementation of accrual accounting with motivation as a moderating variable. This research was conducted in all accounting entities religious ministry in Bali. The number respondents are 98 staff of financial framers, using a saturated sampling technique. The data used is primary data using questionnaires from some previous studies modified by the researcher. Moderated regression analysis with interaction test was used to analyze the data.The test results of hipothesis indicate that competency of human resources has no influence on the implementation of accrual accounting, but information technology gives a positive influenceon the implementation of accrual accounting. The effect of human resource competencies on the implementation of accrual accounting is strengthened by motivation, but motivation it self does not strengthen the influence of Information technology on the implementation of accrual accounting Key words: human resource’s competencies, information technology, motivation, the implementation of accrual accounting.
Keywords: human resource’s competencies, information technology, motivation, the implementation of accrual accounting.